Analisis Regulasi Kawasan Industri Halal dalam Mendukung Pengembangan IKM : Studi Kasus Safe N Lock Sidoarjo, Jawa Timur - Anis Supriyatin; Alifudin Al Azlansyah; Nanda Hanifah; Naerul Edwin Kiky Aprianto (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The Halal Industrial Estate (HIE) in East Java has enormous potential to capitalize on the global trend of increasing demand for halal products. As a country with the largest Muslim population in the world, Indonesia is expected to seize this opportunity through regulations that support the development of HZs, which can not only improve the competitiveness of local products but also expected to contribute to overall economic growth. However, challenges in the development of HEC need to be overcome through close cooperation between the government, industry players, and the community. Socialization of the importance of halal certification and its benefits for Micro, Small and Medium Enterprises (MSMEs) should also be improved to motivate business actors. This study takes a qualitative approach and literature review to understand how government regulations can support the development of the halal industry in Sidoarjo. The findings show that with the right regulations, KIH can function as a halal industry center that meets local needs and can compete in the global market. The strategic steps recommended by the government include increasing local production capacity, strengthening the halal ecosystem from upstream to downstream, and creating a competitive market environment. With these strategic steps, it is expected that East Java can optimize its role in the halal industry.